Bridging the Emotional Gap: Philosophical Insights into Sensual Robots with Large Language Model Technology - Vacura Miroslav (Open Philosophy, 2025)
This article explores the potential of using large language model (LLM) technology in the development of robots to enhance their sociability and sensuality, while also addressing a number of general issues related to human–machine interaction. Based on a philosophical delineation of the foundations of sensuality, the study defines four fundamental characteristics necessary for robots to convincingly simulate social, emotional, and sensory interactions. The text provides an overview of recent advances in social robots and briefly describes LLM technology from both technical and philosophical perspectives. The article highlights the transformative role of LLM in enabling communication, giving an overview of the eight characteristics in which the deployment of this technology represents an advance in human–robot interaction. Robots equipped with LLM technology offer more intuitive and personalized interaction, building on previous communication history, can flexibly adapt to changes in the conversational situation, and understand the subtle nuances of language. They are able to interact emotionally, intimately, and sensually without being judgmental or rejecting users, achieving an emotional connection to the user that robots using traditional technologies have not been able to. At the same time, these new robots have a vast amount of knowledge at their disposal that they are able to use very quickly in communication.